ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM ES TEH DI KOTA SURABAYA - Nuralifia, Dyah Febiyani; Sitohang, Arga Christian (Widya Balina, 2024)
The purpose of this study was to analyze the effect of wages, capital, and production volume on the income of UMKM Es Teh in Surabaya City. This study uses a descriptive quantitative method. Sampling in this study used a saturated sample technique. The sample selected for this study was 40 UMKM es teh in Surabaya City. The findings revealed that wages, business capital and production volume simultaneously did not have a significant effect on income. It is hoped that this information can be input for UMKM es teh actors in determining the wages and business capital used, as well as analyzing the amount of iced tea production each day.